Listeria monocytogenes Associated with New Zealand Seafood Production and Clinical Cases: Unique Sequence Types, Truncated InlA, and Attenuated Invasiveness - Cruz, Cristina D. (American Society for Microbiology, 2014)
Listeriosis is caused by the food-borne pathogen Listeria monocytogenes, which can be found in seafood and processing plants. To evaluate the risk to human health associated with seafood production in New Zealand, multi-virulence-locus sequence typing (MVLST) was used to define the sequence types (STs) of 31 L. monocytogenes isolates collected from seafood-processing plants, 15 from processed foods, and 6 from human listeriosis cases. The STs of these isolates were then compared with those from a collection of seafood isolates and epidemic strains from overseas. A total of 17 STs from New Zealand clustered into two lineages: seafood-related isolates in lineages I and II and all human isolates in lineage II. None of the New Zealand STs matched previously described STs from other countries. Isolates (belonging to ST01-N and ST03-N) from mussels and their processing environments, however, were identical to those of sporadic listeriosis cases in New Zealand. ST03-N isolates (16 from mussel-processing environments, 2 from humans, and 1 from a mussel) contained an inlA premature stop codon (PMSC) mutation. Therefore, the levels of invasiveness of 22 isolates from ST03-N and the three other common STs were compared using human intestinal epithelial Caco-2 cell lines. STs carrying inlA PMSCs, including ST03-N isolates associated with clinical cases, had a low invasion phenotype. The close relatedness of some clinical and environmental strains, as revealed by identical MVLST profiles, suggests that local and persistent environmental strains in seafood-processing environments pose a potential health risk. Furthermore, a PMSC in inlA does not appear to give L. monocytogenes a noninvasive profile.